The influence of the microbiome on radiotherapy and DNA damage responses - Sheikh, Aadil; Curran, Michael A. (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is one of the most prevalent cancers in terms of diagnosis and mortality. Radiotherapy (RT) remains a mainstay of CRC therapy. As RT relies on DNA damage to promote tumor cell death, the activity of cellular DNA damage repair pathways can modulate cancer sensitivity to therapy. The gut microbiome has been shown to influence intestinal health and is independently associated with CRC development, treatment responses and outcomes. The microbiome can also modulate responses to CRC RT through various mechanisms such as community structure, toxins and metabolites. In this review we explore the use of RT in the treatment of CRC and the molecular factors that influence treatment outcomes. We also discuss how the microbiome can promote radiosensitivity versus radioprotection to modulate RT outcomes in CRC. Understanding the molecular interaction between the microbiome and DNA repair pathways can assist with predicting responses to RT. Once described, these connections between the microbiome and RT response can also be used to identify actionable targets for therapeutic development.